2006
DOI: 10.1021/es061000n
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of Perfluorinated Surfactants on Sediments

Abstract: The sorption of anionic perfluorochemical (PFC) surfactants of varying chain lengths to sediments was investigated using natural sediments of varying iron oxide and organic carbon content. Three classes of PFC surfactants were evaluated for sorptive potential: perfluorocarboxylates, perfluorosulfonates, and perfluorooctyl sulfonamide acetic acids. PFC surfactant sorption was influenced by both sediment-specific and solution-specific parameters. Sediment organic carbon, rather than sediment iron oxide content, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

145
944
20
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,174 publications
(1,153 citation statements)
references
References 23 publications
(28 reference statements)
145
944
20
3
Order By: Relevance
“…Partitioning of PFASs onto sediment has been found strongly correlated with sediment TOC (Ahrens et al, 2009b;Higgins and Luthy, 2006). Higgins and Luthy (2006) also found that electrostatic interactions could play a role in sorption of PFASs to sediment.…”
Section: Concentrations and Compositions Of Pfass In Sedimentmentioning
confidence: 81%
See 1 more Smart Citation
“…Partitioning of PFASs onto sediment has been found strongly correlated with sediment TOC (Ahrens et al, 2009b;Higgins and Luthy, 2006). Higgins and Luthy (2006) also found that electrostatic interactions could play a role in sorption of PFASs to sediment.…”
Section: Concentrations and Compositions Of Pfass In Sedimentmentioning
confidence: 81%
“…Perfluorocarbon chain length is the dominant structural feature influencing their partitioning onto sediment (Labadie and Chevreuil, 2011). Partitioning of PFASs onto sediment has been found strongly correlated with sediment TOC (Ahrens et al, 2009b;Higgins and Luthy, 2006). Higgins and Luthy (2006) also found that electrostatic interactions could play a role in sorption of PFASs to sediment.…”
Section: Concentrations and Compositions Of Pfass In Sedimentmentioning
confidence: 86%
“…It was also reported that increasing the pH value decreases the sorption of perfluorinated chemicals on sediments or MWCNTs due to electrostatic repulsion [14]. The further reduction of the adsorption capacity, especially in case of BA above pH 6-7, may also be caused by the increasing negative surface charge of the metallic catalyst.…”
Section: Influence Of Phmentioning
confidence: 96%
“…The partitioning of PFOS between water and suspended sediment particles is crucial for understanding the transport/transform mechanism of PFOS in the environment. Previous studies indicated that PFOS could sorb strongly to sediment when the environmental parameters such as pH, ionic strength and co-solvent were suitable (Higgins and Luthy, 2006;Johnson et al, 2007;Pan et al, 2009). Hydrophobic partition, static attraction, ion-exchange and salting out effect are presumed to be important mechanisms affecting the sorption process (Higgins and Luthy, 2006;Johnson et al, 2007;Pan et al, 2009).…”
Section: Introductionmentioning
confidence: 99%